A note on the core of TU-cooperative games with multiple membership externalities - Heinrich H. Nax (Games, 2014)
A generalization of transferable utility cooperative games from the functional forms introduced by von Neumann and Morgenstern (1944, Theory of Games and Economic Behavior) and Lucas and Thrall (1963, Naval Research Logistics Quarterly, 10, 281-298) is proposed to allow for multiple membership. The definition of the core is adapted analogously and the possibilities for the cross-cutting of contractual arrangements are illustrated and discussed.
Keywords: 330; cooperative games; core; externalities; multiple membership; stability